2021
DOI: 10.1063/5.0032823
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for controlled microwave exposure of aerosolized pathogens

Abstract: A set of three apparatus enabling RF exposure of aerosolized pathogens at four chosen frequencies (2.8 GHz, 4.0 GHz, 5.6 GHz, and 7.5 GHz) has been designed, simulated, fabricated, and tested. Each apparatus was intended to operate at high power without leakage of RF into the local environment and to be compact enough to fit within biocontainment enclosures required for elevated biosafety levels. Predictions for the range of RF electric field exposure, represented by the complex electric field vector magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…SARS-CoV-2 virions have been reported to remain stable and infectious in aerosol for up to 3 hours 10 ; therefore, microwaves with specific frequencies could potentially be used to inactivate SARS-CoV-2 under reasonable microwave power densities that are safe for the human body. Various devices and methodologies have been designed and proposed in order to inspect the inactivation efficacy of the SARS-CoV-2 11 14 , but the correct resonant frequencies remained unknown. Considering the microwave sterilization in public area, microwave frequencies that would resonate with the biological systems should be avoided and the microwave exposure should follow the IEEE safety standards.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 virions have been reported to remain stable and infectious in aerosol for up to 3 hours 10 ; therefore, microwaves with specific frequencies could potentially be used to inactivate SARS-CoV-2 under reasonable microwave power densities that are safe for the human body. Various devices and methodologies have been designed and proposed in order to inspect the inactivation efficacy of the SARS-CoV-2 11 14 , but the correct resonant frequencies remained unknown. Considering the microwave sterilization in public area, microwave frequencies that would resonate with the biological systems should be avoided and the microwave exposure should follow the IEEE safety standards.…”
Section: Introductionmentioning
confidence: 99%
“…When MW acts on bacteria with higher power and longer action time at lethal temperature, the bacterial membrane and cytoplasmic membrane are irreversibly damaged, which can directly lead to bacterial death. This indicates that it is feasible to use MW to kill bacteria and disinfect in the fields of biology and hygiene, and it has been reported (Hoff et al, 2021;Tilley et al, 2021) that MW systems have been implemented for the killing of pathogens in the air.…”
Section: Membrane Levelmentioning
confidence: 99%
“…Given that high-power, long-term MW can effectively destroy bacterial cell membranes to kill bacteria ( Kim et al, 2008 ; Nguyen et al, 2015 ; Park et al, 2017 ; Martinez-Serna et al, 2021 ), MW has shown good development potential in the sterilization and biofilm destruction of laboratory and medical equipment ( Yezdani et al, 2015 ), foods ( Song and Kang, 2016 ; Cho and Chung, 2020 ), and environment ( Mawioo et al, 2016 ; Tong et al, 2016 ). Recently, many microwave systems ( Hoff et al, 2021 ; Tilley et al, 2021 ) have been used for the inactivation of airborne pathogens, and the effect of killing pathogens is remarkable, which gives us hope for the development and application of microwave in vitro sterilization. Since MW is extremely sensitive to changes in surrounding conductivity caused by bacterial growth ( Mohammadi et al, 2020 ; Jain et al, 2021a , b ).…”
Section: Prospects and Challengesmentioning
confidence: 99%
“…For c , we treat the core as a homogeneous diisopropylamine protein solution [13], and for simplification, given the ranges of frequencies used in this paper, we use a dielectric constant of 3.04 [14], [15]. The shell dielectric constant, s is based on the work from Hoff [16], and ranges between 2 − 27. Figure 3 plots both the range of effective permittivity which are going to be used for the calculations for the reminder of this work, and the calculated enclosed charge as a function of the shell's dielectric constant.…”
Section: Em Scattering Properties Of Virion a Core-shell To Homogeneo...mentioning
confidence: 99%